Santiago Ramón y Cajal - Moreno, Iveth (2021)
Don Santiago Ramón y Cajal, was a Spanish medical scientist and artist, who fascinated the world with his research on the nervous system. This article presents a brief biography of his life, from his childhood until his death; on how his father impacted his life and how his tenacity led him to be awarded the most important prize for a scientist, the Nobel Prize.